Medical electronics [technology 1999 analysis and forecast]. - Lazarus-Karaoglan, T. (IEEE spectrum)
By taking technologies already in use, experimenters hope to help the arthritic, the nearsighted, and those with internal disorders. And a novel bone technique has just obtained premarket approval from the US Food and Drug Administration (FDA), Rockville, Md. Optical coherence tomography, originally developed to image eye tissues and artery-clogging plaques, is now being enhanced for the early detection of joint disease. Microwave heating is being developed to correct misshapen corneas found in visual disorders like myopia. In a magnetic resonance imager, a superconducting probe is shown to provide clearer images than a probe at room temperature. And the FDA action applies to a portable, noninvasive unit that uses an electromagnetic field to stimulate bone growth